The Ideal 2024 Election Based on The Study of Decisions of The Republic of Indonesias Constitutional Court - Munadi, Munadi Munadi; Nuzulia, Qoriatun (Unnes Political Science Journal, 2023)
The first election process in Indonesia was the holding of simultaneous elections on April 17 2019. This was a consequence of the Constitutional Court Decision 14/PUU/2013 concerning the review of Law 42 of 2008 concerning the General Election of the President and Vice President. Although the simultaneous election is considered superior to the previous election, its implementation is not without flaws. The issue that was most shocking was the large number of fatalities caused by election organizers, which were allegedly caused by other technical problems and the 2019 simultaneous local elections. Based on the Constitutional Court Decision Number 55/PUU-XVII/2019, the Association for Elections and Democracy (Perludem) conducted a judicial review The 1945 Constitution by considering the various parties that emerged from the 2019 Election. The Petitioner conveyed a number of points in his argument related to the analysis of how the 2019 simultaneous elections were held yesterday. The Constitutional Court ruled that the petition had no legal basis, so that the petition was rejected completely. However, in accordance with the 1945 Constitution, the Constitutional Court provides an alternative model of simultaneous elections that can be chosen and considered constitutional. The research method used is the normative juridical method, which is meant by "normative juridical" is a type of procedural scientific investigation of the scientific logic of law, especially based on norms, to find facts. Qualitative studies are used in the data collection and argumentation methods of this paper, in particular by collecting various primary and secondary scientific reference sources from related writings such as books, journals, papers and mass media news about the impact of holding the 2019 simultaneous elections and their impacts. efficacy. refuses to hold simultaneous elections in 2024. In qualitative research, data is collected continuously until it is saturated from various sources using various data collection methods. A comprehensive analysis is needed of the 2024 election model by looking at the findings. All aspects must be considered, starting from the impact on voters, political parties, election administrators, to presidential and regional government systems. The national general election to simultaneously elect members of the DPR, DPD, and President/Vice President is the ideal election model discussed in this paper. After that, governors, regents and mayors are elected simultaneously in regional head elections for the provincial DPRD, regency/city DPRD and governor. In addition, the government can advance the holding of simultaneous elections in 2024 by utilizing technology with the e-voting system to support the performance of election organizers. The author hopes that the shortcomings and problems of the previous election can be a lesson during the upcoming 2024 election. It is hoped that all parties are ready to hold democratic general elections. Of course, public participation in the general election is also highly anticipated. Respect each other's choices without jeopardizing family relationships.